Analisis Pengaruh Penanaman Modal Asing, Penanaman Modal dalam Negeri, Belanja Daerah, dan Tenaga Kerja terhadap Pertumbuhan Ekonomi di Pulau Kalimantan 2015-2024 - Wulan Wahyu Ning Tias; Risdiana Himmati (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the impact of Foreign Direct Investment (FDI), Domestic Investment (DDI), regional spending, and labor on economic growth in Kalimantan Island during the period 2015–2024. Economic growth is measured by the growth rate of the Gross Regional Domestic Product (GRDP) of the five provinces on the island of Kalimantan. This study uses a quantitative approach with a panel data regression method that combines time series and cross-sectional data. The estimation model was selected through Chow and Hausman tests, which showed that the Fixed Effect Model (FEM) was the best model. Simultaneous test results show that foreign direct investment (FDI), domestic investment, regional spending, and labor collectively have a significant effect on economic growth. However, in part, domestic investment has a positive and significant effect on economic growth, while foreign direct investment, regional spending, and labor do not have a significant effect. These findings indicate that domestic investment plays a dominant role in driving regional economic growth in Kalimantan, while the effectiveness of foreign investment, regional spending, and the role of labor still need to be optimized through development policies oriented towards increasing productivity, human resource quality, and the efficiency of regional government spending.